2017
DOI: 10.1007/s00406-017-0774-1
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in the dorsal raphe nucleus plays a potential role in both suicide facilitation and prevention in affective disorders

Abstract: An involvement of the central serotonergic system has constantly been reported in the pathogenesis of suicide. The dorsal raphe nucleus (DRN) is the main source of serotonergic innervation of forebrain limbic structures disturbed in suicidal behaviour, in which an abnormal microglia reaction seems to play a role. In our present study, the density of microglia immunostained for the HLA-DR antigen was evaluated in the DRN. These analyses were carried out on paraffin-embedded brains from 24 suicidal and 21 non-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 70 publications
4
46
0
2
Order By: Relevance
“…We cannot necessarily conclude that neuroinflammation is absent in those with normal or lowered TSPO as increased levels of inflammatory cytokines can occur with a downregulation (rather than upregulation) of TSPO (72). Nevertheless, the pattern of TSPO availability in our patients is consistent with recent postmortem findings of significantly decreased microglial activation in non-suicidal depressed patients compared to suicidal depressed patients and controls in the dorsal raphe nucleus, which provides the major serotonergic innervation to the ACC, PFC and insula (48). This is particularly interesting given recent evidence that abnormal 5-HT function measured using PET predicts higher suicidal ideation and more lethal suicidal behavior (80).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We cannot necessarily conclude that neuroinflammation is absent in those with normal or lowered TSPO as increased levels of inflammatory cytokines can occur with a downregulation (rather than upregulation) of TSPO (72). Nevertheless, the pattern of TSPO availability in our patients is consistent with recent postmortem findings of significantly decreased microglial activation in non-suicidal depressed patients compared to suicidal depressed patients and controls in the dorsal raphe nucleus, which provides the major serotonergic innervation to the ACC, PFC and insula (48). This is particularly interesting given recent evidence that abnormal 5-HT function measured using PET predicts higher suicidal ideation and more lethal suicidal behavior (80).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, a higher degree of suicidal ideation has been associated with an increased inflammatory index, independent of severity of depressive symptoms (45). Multiple postmortem studies have found evidence for inflammation in the brains of suicide victims (46,47), with specific evidence for activated microglia in the ACC and PFC of depressed individuals who had committed suicide (32,33), and significantly less microglial activation in the dorsal raphe nucleus in non-suicidal depressed patients who had died of other causes compared to suicidal depressed patients and controls (48). However, no study to date has investigated the association between neuroinflammation and suicidality in depression in-vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found significant associations between genes with known immune functions and diseases that include Alzheimer's Disease and schizophrenia (Sekar et al, 2016;Henstridge et al, 2019;Kunkle et al, 2019;Mathys et al, 2019). Pro-inflammatory signaling and immunological perturbations in the dorsal raphe nucleus (DRN), the largest serotonergic center in the brain, have also been implicated in behavioral and mood disorders that include impulsivity, major depressive disorder, and bipolar disorder (Mahmood and Silverstone, 2001;Baumann et al, 2002;Matthews and Harrison, 2012;Howerton et al, 2014;Brisch et al, 2017). Microglia, the predominant resident immune cells of the central nervous system (CNS), express many of these disease-associated genes and undergo transcriptional changes and diversification in both acute and chronic models of inflammation, aging, and neurodegeneration (Mrdjen et al, 2018;Hammond et al, 2019;Jordão et al, 2019;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia cells have been shown to play an important role in the pathophysiology of MDD [ 25 , 140 ]. Additionally, the status of microglial activation and inflammation also appear to be associated with stress vulnerability and resilience.…”
Section: Microglia and Inflammation In The Resilience To Stressmentioning
confidence: 99%